PERCEIVED ANXIETY OF ENGLISH LEARNER AND TEACHER IN A CALL ENVIRONMENT CLASSROOM - Ocampo, Merissa (PEOPLE: International Journal of Social Sciences, 2017)
This exploratory study examines Foreign Language Anxiety of both English as a Foreign Language (EFL) teachers and learners in a Computer Assisted Language Learning (CALL) environment. Many studies have focused on students’ anxieties but overlooked the possibility that teachers may also experience anxiety, potentially harming foreign language teaching delivery. The result of this study revealed that teachers experienced a double impact of the intense feeling of anxiety and worry about how to cope with teaching Grammar, Communication, and Reading with a combination of CALL gadgets in a CALL environment. While the English learners in this study, being computer science majors, were not impacted by stress to the same degree when following instructions on how to use such gadgets. Among student concerns, deep anxiety was only experienced by learners if a sudden shift between using computer screen and whiteboard occurred in the course of instruction